Improving production efficiency at DIGI Camera, Malaysia - Nagappan, Venkateswaran; Sambasivan, Murali (Universiti Putra Malaysia Press, 2008)
The case discusses the problems in achieving production efficiency at DIGI Camera, Malaysia. The parent company was established in Japan in 1928 and since then, had been consistently introducing new and advanced technologies in their line of products. The company introduced digital lens cameras in March 2001 and was struggling to meet the production targets because of high rejection rates. The company was respected for its high quality products and the current situation was completely unacceptable to the company’s top management. Through systematic analysis, the causes for high rejection rates were identified. The case provides information on the costs and benefits that could be obtained by eliminating these causes. This study illustrates how systematic analysis of quality problems can help generate viable solution alternatives and can help select the best alternative to implement.